2017
DOI: 10.1002/micr.30129
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous vascularized bony reconstruction of the maxilla and mandible using a single fibula: A case report

Abstract: Simultaneous maxillary and mandibular reconstruction is exceedingly rare. These are complicated cases, requiring consideration of multiple variables: defect components, donor site morbidity, recipient vessels, and so forth. We describe a unique case of secondary maxillary/mandibular reconstruction in a 59-year-old male. The original defect was created after removal of a buccal squamous cell carcinoma, involving the external cheek skin, buccal mucosa, right mandibular body, and right inferior maxilla; a free ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Defects similar to those discussed herein historically have been addressed either with multiple free flaps placed simultaneously(Ozkan et al, 2004; Punpale et al, 2006) or a single free tissue transfer split into two separate bony segments(Coleman 3rd & Sultan, 1991; Laure et al, 2008; Mericli et al, 2017; Punpale et al, 2006; Sadove & Powell, 1993). Utilizing a single free flap has multiple advantages, including reducing donor site morbidity and operative time, while preserving other donor sites as potential reconstructive options should initial efforts fail (Laure et al, 2008; Nguyen et al, 2013; Punpale et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Defects similar to those discussed herein historically have been addressed either with multiple free flaps placed simultaneously(Ozkan et al, 2004; Punpale et al, 2006) or a single free tissue transfer split into two separate bony segments(Coleman 3rd & Sultan, 1991; Laure et al, 2008; Mericli et al, 2017; Punpale et al, 2006; Sadove & Powell, 1993). Utilizing a single free flap has multiple advantages, including reducing donor site morbidity and operative time, while preserving other donor sites as potential reconstructive options should initial efforts fail (Laure et al, 2008; Nguyen et al, 2013; Punpale et al, 2006).…”
Section: Discussionmentioning
confidence: 90%
“…Nguyen et al detailed the use of a single fibula to reconstruct a simultaneous maxillary and mandibular defect by splitting the pedicle and using two different anastomoses(Laure et al, 2008), which is similar to the reconstruction detailed by Mericli et al, who reported the use of a single fibula to create two free flaps(Mericli et al, 2017). Important aspects to consider is the location of the defect detailed by Nguyen et al, which was contralateral and relatively posterior, requiring a shorter individual pedicle for each flap; and the need for an anterolateral thigh free tissue transfer to accompany the fibula free flaps in order to reconstruct the soft tissue and external skin defects in the report by Mericli et al In contrast, our case series expands upon the use of the single fibula free flap with a single pedicle to reconstruct a defect that spans to the maxillary midline and does not require a separate accompanying soft tissue free flap.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…mandible defects with good outcomes (Krane et al, 2021;Laure et al, 2008;Mericli et al, 2017). On the other hand, new technologies and preoperative virtual planning provide help to surgeons with the number and placement of the osteotomies, optimizing the possibilities for complex bone reconstruction with a single flap (Kääriäinen et al, 2016;Powcharoen et al, 2019).…”
mentioning
confidence: 99%